2014
DOI: 10.1039/c4ib00025k
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic morphology: biophysical indicators for iron-driven inflammatory diseases

Abstract: Most non-communicable diseases involve inflammatory changes in one or more vascular systems, and there is considerable evidence that unliganded iron plays major roles in this. Most studies concentrate on biochemical changes, but there are important biophysical correlates. Here we summarize recent microscopy-based observations to the effect that iron can have major effects on erythrocyte morphology, on erythrocyte deformability and on both fibrinogen polymerization and the consequent structure of the fibrin clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 360 publications
4
147
0
1
Order By: Relevance
“…in ref. [86][87][88], but both converge on terminal steps in which prothrombin is converted Fig. 1 Some risk factors, associated with hypercoagulability.…”
Section: Relationship Between Chronic Inflammation and Hypercoagulabimentioning
confidence: 99%
See 1 more Smart Citation
“…in ref. [86][87][88], but both converge on terminal steps in which prothrombin is converted Fig. 1 Some risk factors, associated with hypercoagulability.…”
Section: Relationship Between Chronic Inflammation and Hypercoagulabimentioning
confidence: 99%
“…ref. 88,[366][367][368][369][370][371][372][373][374][375][376], and fibrin clot properties also vary in this way with various diseases (e.g. ref.…”
Section: Effects Of Fibrinogen Concentration On the Nature Of The Clotmentioning
confidence: 99%
“…Several diseases influence the functions of various cytoskeleton proteins [51][52][53], such that they often change cell shapes and the ultra-structures of cell membranes. Buys et al showed that the membrane roughness of red blood cells (RBCs) obtained from diabetes patients were correlated with the disease status [54].…”
Section: Discriminating Ill Cells From Healthy Onesmentioning
confidence: 99%
“…[5] A recent review by Pretorius and Kell provided an overall view of biophysical properties of RBCs, correlations with fibrin and ferritin profile and its implications in pathorheology of vascular disorders. [6]. However, the focus on the flow of RBCs was limited.…”
Section: Introductionmentioning
confidence: 99%